Outcomes of chronic pectoralis major rupture repair with implant-free Achilles allograft - Abdul-ilah Hachem, MD; Diego Gonzalez-Morgado, MD; Peio Beristain, MD; Gonzalo Barraza, MD; Fernando Alvarado, MD; Karla Bascones, MD; Amr Elmaraghy, MD; Xavi Rius, MD (JSES Reviews, Reports, and Techniques)
Background: Pectoralis major tendon (PMT) ruptures are on the rise. Although early surgical repair of PMT ruptures is recommended, some present in a delayed manner, making chronic ruptures more challenging to repair. Although multiple techniques involving different grafts and fixation methods have been described, a standardized approach is lacking. This study aimed to report the clinical outcomes of patients who underwent reconstruction of chronic PMT ruptures using Achilles tendon allograft fixed with implant-free transosseous sutures. Methods: A retrospective review of patients who underwent PMT reconstruction with a minimum follow-up of 2 years. Patient demographics, delay in diagnosis and treatment, and follow-up were recorded. Patient-reported outcome measures were recorded at baseline and the final follow-up. These outcomes included the American Shoulder and Elbow Surgeons score, visual analog scale for pain, Constant score, and subjective shoulder value. At the last follow-up, the postoperative ranges of motion and adduction isometric strength were compared with those of the uninjured arm. Additionally, postoperative complications, return-to-previous activities, cosmetic appearance, and overall patient satisfaction were documented. Results: Four male patients with a median age of 46.5 years (29-52) were included. The mean delay in diagnosis and treatment was 5.5 months (2-12) and 12 ± 4.9 months, respectively. The overall cohort improved significantly regarding pain (visual analog scale: −6 [95% CI: −2.3 to −9.7], P = .014) and patient-reported outcome measures (American Shoulder and Elbow Surgeons: 23 [95% CI: 14.6-31.4], P = .003; Constant score: 38.8 [95% CI: 9.3-68.2], and P = .025; subjective shoulder value: 45 [95% CI: 0.5-89.5], P = .049). All patients had full range of motion with no differences between the sides (forward flexion: 180° ± 0, external rotation 81° ± 9, and internal rotation: T7 ± 1). The mean adduction strength for the injured side was 21 ± 3.9 kg, with no difference compared to the uninjured side (21 ± 6.7 kg, P = 1). All patients were satisfied and returned to their previous activities; no postoperative complications were reported. Conclusion: Chronic PMT rupture reconstruction with Achilles tendon allograft fixed with implant-free transosseous sutures provides excellent clinical outcomes and strength restoration with high satisfaction and low complication rates.